Population dynamics and transcriptomic responses of Pseudomonas aeruginosa in a complex laboratory microbial community - Cheng, Yingying (2019)
Pseudomonas aeruginosa tends to be among the dominant species in multi-species bacterial consortia in diverse environments. To understand P. aeruginosa’s physiology and interactions with co-existing bacterial species in different conditions, we established physiologically reproducible 18 species communities, and found that P. aeruginosa dominated in mixed-species biofilm communities but not in planktonic communities. P. aeruginosa’s H1 type VI secretion system was highly induced in mixed-species biofilm consortia, compared with its monospecies biofilm, which was further demonstrated to play a key role in P. aeruginosa's enhanced fitness over other bacterial species. In addition, the type IV pili and Psl exopolysaccharide were required for P. aeruginosa to compete with other bacterial species in the biofilm community. Our study showed that the physiology of P. aeruginosa is strongly affected by interspecies interactions, and both biofilm determinants and type VI secretion system contribute to higher P. aeruginosa's fitness over other species in complex biofilm communities.